(NpROEKTIROWANIE I SOSTAWLENIE KART (B:s ((NoB]AQ ^ASTX(B. (NtEORIQ I PROCESSY LABORATORNOGO IZGOTOWLENIQ KART(B) : (Nu^EBNOE POSOBIE (B/s - (NsALI]EW(B, (NkONSTANTIN aLEKSEEWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 232 (6 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 233-238s
Keywords: (NkARTOGRAFIQs